Housing Cooperatives, Housing Affordability, and Rent Control - Matthias Wrede (CESifo GmbH, 2024)
Housing cooperatives have a significant share in some countries, particularly in urban housing markets, and are supported by municipalities through tax breaks and preferential access to land. We examine the contribution of housing cooperatives to the provision of affordable housing and how they are affected by rent control. For Germany, we find that residents of cooperative housing pay lower rents than for-profit owners, but are still affected by rent control. In particular, we show that stricter limits on rent increases for existing residential leases in tight housing markets have the effect of lowering rents for housing cooperatives, while we find no such effect of rent regulation for for-profit landlords.
Keywords: P13; R21; R31; R38; 330; housing affordability; housing cooperatives; housing tenure; rent control